Dispositif Hybride De Formation Universitaire Des Enseignants : Etude De Cas - Zeitoun, Samar; Malek, Rima (European Scientific Journal, ESJ, 2018)
The adoption of blended learning is an under-researched process in the Lebanese academic context, especially when students are teachers in professional development. Although the movement towards blended learning is generally initiated in some university courses, little research has investigated teachers' perceptions of the factors that determine their success and minimize resistance, especially at the level of delivery. This article explores the adoption of hybrid training in a course at the Lebanese university. This case study explores, based on the questionnaires administered to a sample of 65 trainee teachers, the concept of blended learning from their points of view. The questionnaire included five main lines based on the literature such as (a) learning process, (b) trainer support, (c) equipment, (d) collaboration and (e) technology. The results indicated that teachers were satisfied with both their participation in the course and the knowledge gained during the training as well. The results also revealed a number of factors to consider when designing such courses in the Lebanese context.